A Study on Financial Literacy among Senior Secondary Students: Exploring the Implications and Benefits - Chaurasia, Deeksha; Ravichandran, R. (JOURNAL OF INDIAN EDUCATION, 2026)
This paper explores the importance of financial literacy for school students in India. With the ever-growing complexity of financial systems, it has become crucial for individuals to possess financial knowledge and skills to make informed decisions. However, the lack of financial education in schools often leads to poor financial management and decision-making, resulting in financial insecurity and debt. This paper highlights the study on financial literacy among senior secondary students, exploring the implications, and discussing the benefits and challenges of implementing such programmes. It also analyses the current state of financial literacy among school students in India and proposes recommendations for improving financial education. The paper concludes that providing financial education to school students is essential to equip them with the necessary knowledge and skills to make informed financial decisions, ensuring their financial well-being and contributing to the growth of the Indian economy.